THE IMPLEMENTATION OF ROLE PLAY IN TEACHING SPEAKING: An Experimental Study to The Second Years Students of Ma Putra Al-Islahuddiny Kediri Lombok Barat In Academic Year 2017/2018 - SARIFUDDIN MUHAMAD (Universitas Pendidikan Mandalika, 2017)
ABSTRACT: This study was designed to improve the students’ speaking ability using role play. The study was intended to describe how role play can improve the speaking ability of the second years’ student of MA PUTRA AL-ISLAHUDDINY Kediri Lombok Barat. This research was an experimental research in which the researcher employed the two group design where the control and experimental group were given pretest before treatment and posttest after the different treatment have been given. The population of this research was the second grade students of MA PUTRA AL-ISLAHUDDINY Kediri Lombok Barat in academic year 2017/2018 while the sample for this research was taken using cluster random sampling technique, then taken XI A as the experimental group and XI B as the control group. The finding of the study revealed that role play was successful in improving students’ speaking ability. Data obtained for the students’ speaking ability from the two groups were analyzed using t test formula to determine degree of significant of the differences between two groups. Based on the test data analysis found the mean score of experimental class was higher than the mean score of control class (MX= 6, 80 > MY = 4, 86 ) then further analyzed using t test, found that t count > t table that was t count = 0,1 % or 0,99 is 2,42 and t table = 0.95 or 0,5% is 2,68. It is found that 3, 35 is higher than 2,42 and 2,68. So level of significant and according to the existing criteria that the differences between control group and experimental group was significant.Keyword: Role play and Speaking Aability